Influence of carbohydrate fractions on degradability, rumen fermentation, and methane emission in selected tropical forages using an in vitro study - Ridla, Muhammad; Abdullah, Luki; Ernawati, Azib (Agriculture and Natural Resources, 2025)
Importance of the work: Understanding of how forage composition affects energy production, nutrient utilization, and methane emissions in ruminants has been enhanced, supporting the development of feeding strategies that improve animal productivity while reducing environmental impact. Objectives: To examine the contribution of carbohydrates to in vitro degradability, rumen fermentation, methane emission, and their interrelationships. Materials and Methods: Six forage types were evaluated: the Pakchong and Taiwan cultivars of Napier grass (Pennisetum purpureum), the Samurai 1 and Samurai 2 varieties of sorghum (Sorghum bicolor), sweet corn (Zea mays saccharata), and branches of Indigofera zollingeriana. The study specifically examined the contribution of carbohydrates to in vitro dry matter and organic matter degradability, ruminal fermentation characteristics (pH, ammonia concentration, short-chain fatty acids (SCFAs), and total gas production), methane emissions, and their interrelationships. A completely randomized design was used with the six forage types as treatments, each replicated five times. A randomized group design was used for the in vitro fermentation study. Data were analyzed using analysis of variance, and treatment means were compared using Tukey’s post hoc test. Results: There were significant (p < 0.05) differences in the nutrient contents among the various selected forages tested based on dry matter, crude ash, crude protein, ether extract, crude fiber, and non-fibrous carbohydrates, as well as structural carbohydrates (neutral detergent fiber and acid detergent fiber) and nonstructural carbohydrates (total sugars and starch). Structural carbohydrates were negatively (p < 0.05) correlated with forage degradability, total SCFAs, and gas production, while nonstructural carbohydrates were positively (p < 0.05) correlated with these factors. There was an inverse correlation with methane emission, indicating the potential of carbohydrates as indicators for ruminal nutrient fermentation. Main finding: Methane mitigation could be achieved by selecting forage types low in structural and high in nonstructural carbohydrates.